Geological influence on hydrochemical dynamics and fluoride contamination of groundwater from granitoid province in Central India - Seema Yadav; Rimjhim Singh; Pramod Kumar Singh; Shalini Maurya; Abhinandan Srivastava; Ajay Kumar Talwar (Environmental Advances, 2025)
Fluoride (F−) in groundwater poses serious health risks worldwide, particularly in semi-arid regions. Understanding contamination levels, hydrogeochemical processes, and evaluating their potential human health risks are crucial for developing effective management strategies. In this study, we investigated the spatial distribution and geochemical mechanisms of F− contamination in Sonbhadra district, Uttar Pradesh (Central India), using petrographic-mineralogical analysis, hydrochemistry, and multivariate statistical techniques. Additionally, we explored the impact of human activities, including land-use changes, on groundwater quality in the region. Groundwater samples from 199 sites were analyzed for major and minor ions, while petrological and mineralogical analyses of rocks were conducted to identify F− bearing mineral phases. Groundwater F− levels varied from 0.1 to 9 mg/L, averaging 1.39 mg/L, with 46% of samples exceeded the WHO guideline value (1.5 mg/L). Hydrochemical data indicated that groundwater quality was primarily influenced by water-rock interactions, silicate weathering, and ion exchange processes, while the impact of anthropogenic activities was relatively minor. The F− levels exhibited a positive relationship with Na+ and HCO3− concentrations, confirming F− release due to silicate mineral weathering. Petrographic and mineralogical analyses indicated that the F− in groundwater primarily originates from weathering-dissolution of flouride containing minerals like fluorite, biotite and apatite as well as amphibole, epidote, and sphene present in the granitoid rocks. The hazard quotient (HQFluoride) values exceeded unity in 21.60% of samples for adults, 57.28% for children, and 62.81% for infants, highlighting that children and infants are at a higher risk of non-carcinogenic health effects compared to adults.